Renovation and maintenance project at Pertubuhan Peladang kawasan Padang Rengas fertilizer store / Nurul Hanis Azmi - Azmi, Nurul Hanis (Universiti Teknologi MARA UiTM,Perak, 2022)
Industrial training refers to the placement of students in an organization to undertake supervised practical training in a selected industry, either abroad or within the country, within a specified period of time before they are awarded a recognized Certificate or Degree. It is a mandatory course for all degree students of Building Surveying Department. It is a requirement to fulfil the course in order to complete the degree as well as graduate from the university. Practical training or industrial training is a compulsory course for all undergraduate students of the Building Surveying Department. It is a requirement to meet the course requirements to complete the degree so that students can graduate from university. With this industrial training, it can increase the level of work ability of graduates as well as be able to expand the opportunities of students in the world of work to receive experience. This is because, the graduates must have relevant and up to date knowledge, practical experience, soft skills as well as a positive attitude to equip the graduates before facing the challenges of the real career situation.